Association Between Tuberculosis and Parkinson Disease: A Nationwide, Population-Based Cohort Study. Issue 8 (February 2016) - Shen, Chih-Hao; Chou, Chung-Hsing; Liu, Feng-Cheng; Lin, Te-Yu; Huang, Wen-Yen; Wang, Yu-Chiao; Kao, Chia-Hung
Abstract : Abstract: Few studies have investigated the association between tuberculosis (TB) and Parkinson disease (PD). This nationwide, population-based, retrospective cohort study investigated the risk of PD in patients with TB. We selected patients newly diagnosed with TB (International Classification of Diseases, Ninth Revision, Clinical Modification: 011) from 2000 to 2009 in the Taiwan National Health Insurance Database as the TB cohort. The comparison cohort (the non-TB cohort) was frequency matched to the TB cohort at a ratio of 4:1 by sex, age, and the index date. We analyzed the risks of PD by using Cox proportional hazard regression models. A total of 121, 951 patients with TB and 487, 800 non-TB controls were enrolled in this study. The TB cohort had a 1.38-fold risk of PD compared with the non-TB cohort after adjustment for age, sex, and comorbidities (aHR, 95% CI: 1.30–1.46). The adjusted risk of PD in the TB and non-TB cohorts increased in subgroups regardless of age, sex, and comorbidities. Combined effect of TB and comorbidities on the risk of PD were significant in patients with TB who had diabetes (aHR: 2.26, 95% CI: 2.02–2.52), hypertension (aHR: 2.23, 95% CI: 2.04–2.44), head injury (aHR: 2.32, 95% CI: 1.95–2.77), chronic kidney disease (aHR: 2.02, 95% CI: 1.49–2.72), chronic obstructive pulmonary disease (aHR: 1.84, 95% CI: 1.66–2.05), depression (aHR: 4.66, 95% CI: 3.59–6.05), dementia (aHR: 3.70, 95% CI: 2.99–4.59), and stroke (aHR: 2.56, 95% CI: 2.28–2.87). The risk of PD was higher in a follow-up within 1 year (aHR: 1.78, 95% CI: 1.58–2.00) and decreased with the follow-up period in the TB cohort. Patients with TB have an independently 1.38-fold risk of PD. The risk of PD decreased with the follow-up period in the TB cohort. Physicians should be aware of the risk of PD in patients with TB when treating such patients.